Digital Marketing Strategy And Social Media For Culinary Business - Achmad Zulfikar Siregar; Fajar Maulana (SEAN Institute, 2022)
Social media users are currently an opportunity for Micro, Small and Medium Enterprises (MSMEs) to market their products, which is known as the previous digital marketing strategy, replacing traditional marketing strategies. The new digital marketing strategy was applied to the Pala Nusantara Small and Medium Enterprises, which previously only did marketing by offering products to stores. Assessment of effectiveness in digital marketing uses the theory of Marketing Communication Integration as a communication tool in conveying information to consumers. sales time by business owners can be done at any time, purchases can be made instantly so that for business owners using marketing on social media it becomes effective in terms of receipts from sales made and benefits for consumers, namely it is more efficient in buying products without having to go to the store. You need to understand that in building a culinary business, not only taste is the main thing for a culinary business. But also packaging, product photos, and so on are also the main attraction for potential buyers.